Second Pathways in the Pathophysiology of Ischemic Priapism and Treatment Alternatives - Karakeci, Ahmet; Firdolas, Fatih; Ozan, Tunc; Unus, Ihsan; Ogras, Mehmet Sezai; Orhan, Irfan (Elsevier Science Inc, 2013)
OBJECTIVE To evaluate the early therapeutic alternatives such as bosentan, an endothelin receptor blocker, theophylline, an adenosin receptor blocker, and a nonselective phosphodiesterase enzyme inhibitor, zinc protoporphyrin (ZnPP), a heme oxygenase 1 inhibitor, for the therapy of ischemic priapism in the rat models. METHODS Twenty-four Sprague-Dawley rats were randomly divided into 4 equal groups: control group, ZnPP group, bosentan group, and theophylline group. Erection was provided by vacuum constriction method and maintained for 4 hours for achieving the priapism in all groups. The rats in the control group were administered 1 mL/kg saline intraperitoneally (ip). The rats in group 2 were administered 25 mg/kg ZnPP ip. The rats in group 3 were administered 0.25 mg/kg bosentan ip. The rats in group 4 were administered 100 mg/kg theophylline ip. Six rats from each group were decapitated after 6 hours of drug administration. Then endothelin 1, adenosine deaminase, heme oxygenase 1 enzymatic activity, and apoptosis index in the cavernous tissues were estimated. RESULTS Cavernous tissue endothelin 1, adenosine deaminase, heme oxygenase 1 enzymatic activity levels, and apoptosis index were significantly decreased in bosentan, theophylline, and ZnPP-treated rats compared with the controls. CONCLUSION Inhibition of priapism induced apoptosis with bosentan, theophylline, and ZnPP seems promising on preserving erectile function. UROLOGY 82: 625-629, 2013. (C) 2013 Elsevier Inc.
Keywords: Adenylate-Cyclase; Heme Oxygenase-1; Adenosine; Inhibition; Monoxide; Tissues